Piecewise-maximum closed Geodesic trajectories on bounded Toroidal manifolds - Romanov, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We use toroidal coordinates for the investigation of maximum geodesic trajectories for arbitrary parameters of a torus. Conditions under which trajectories are located in a bounded part of the toroidal manifold are considered. Using global invariants, we construct closed piecewise-maximum geodesic trajectories.